Perspektif Teologi Tubuh dalam Memahami dan Menolong Depresi Remaja Penderita Depresi - Christian, Ivan; Farrand, Peter (Verbum Christi: Jurnal Teologi Reformed Injili, 2024)
The high prevalence of teenage depression in Indonesia warrants serious attention. Adolescents need assistance in effectively overcoming their depression to undergo a transformative process. This paper aims to elucidate a theological perspective on the body as a normative foundation for Christians to comprehend adolescents’ depression thoroughly and provide appropriate assistance. The research methodology employed in this study is the practical theology method advocated by Richard Osmer. The findings reveal that depression and its associated symptoms are not inherent designs of God for humans, who are "embodied beings." Adolescent depression disrupts the entirety of their selves, including their bodies. Furthermore, adolescents have the potential for transformation if depression is addressed holistically, considering both material and non-material aspects of an individual.